MAGNETIC AND TRANSPORT PROPERTIES OF DOUBLE PEROVSKITES - BURZO, Emil (Studia Universitatis Babeș-Bolyai Chemia, 2021)
The magnetic and transport properties of polycrystalline Sr2FeMoO6 perovskites are strongly dependent on their microstructure. A cluster glass type behavior was shown at the grain boundaries. The increase of the sintering time from 4 to 8 hrs in Sr2FeMo1-xWxO6 and Ca1.5La0.5FeMo1-xWxO6 series improves the crystallographic order. As a result there is an increase of both the saturation magnetizations and of spin polarizations.